Estimation of Cardiovascular Risk in Patients with Type 2 Diabetes - Belkis Vicente Sánchez; Ernesto Vicente Peña; Miriam Costa Cruz (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Background: diabetes mellitus accelerates atherosclerotic changes throughout the vascular tree and consequently increases the risk of developing fatal acute events. Objective: to estimate the global cardiovascular risk in patients with type 2 diabetes mellitus. Method: a cross-sectional study of a series of type 2 diabetic patients from the People's Council of Constancia, Abreus municipality, Cienfuegos province was conducted from July to December 2012. The universe comprised the 180 people with diabetes in the area. Variables studied were: age, sex, body mass index, nutritional assessment, blood pressure, toxic habits, associated chronic diseases, blood levels of glucose, lipids (total cholesterol and triglycerides) and microalbuminuria. World Health Organization/International Society of Hypertension prediction charts specific to the region of the Americas, in which Cuba is included, were used to estimate the cardiovascular risk. Results: mean age was 61.63 years and females predominated. Relevant risk factors were hypertension followed by obesity, smoking and dyslipidemia. Mean body mass index was 27.66kg/m2; waist circumference was 94.45 cm in women and 96.86 cm in men. Thirty point six percent had more than two uncontrolled risk factors and 28.3 % of the total presented a high to very high cardiovascular risk. Conclusions: cardiovascular risk prediction charts are helpful tools for making clinical decisions, but their interpretation must be flexible and allow the intervention of clinical reasoning.